Psychotropic drugs and risk of motor vehicle accidents: a population‐based case‐control study - Chang, Chia‐Ming; Wu, Erin Chia‐Hsuan; Chen, Chuan‐Yu; Wu, Kuan‐Yi; Liang, Hsin‐Yi; Chau, Yeuk‐Lun; Wu, Chi‐Shin; Lin, Keh‐Ming; Tsai, Hui‐Ju (British journal of clinical pharmacology, 2013)
Aim To examine comprehensively the relationship between exposure to four classes of psychotropic drugs including antipsychotics, antidepressants, benzodiazepines (BZDs) and Z‐drugs, and motor vehicle accidents (MVAs). Method The authors conducted a matched case‐control study of 5183 subjects with MVAs and 31 093 matched controls, identified from the claims records of outpatient service visits during the period from 2000 to 2009. Inclusion criteria were defined as subjects aged equal to or more than 18 years and involved in MVAs. Conditional logistic regressions with covariates adjustment (including urbanity, psychiatric and non‐psychiatric outpatient visits and Charlson comorbidity score) were applied to examine the effect of four classes of psychotropic drugs on MVAs. Results Significant increased risk of MVAs was found in subjects taking antidepressants within 1 month (adjusted odds ratio (AOR) 1.73, 95% confidence interval (CI) 1.34, 2.22), 1 week (AOR 1.71, 95% CI 1.29, 2.26), and 1 day (AOR 1.70, 95% CI 1.26, 2.29) before MVAs occurred. Similar results were observed in subjects taking benzodiazepines (BZDs) (AOR 1.56, 95% CI 1.38, 1.75 for 1 month; AOR 1.64, 95% CI 1.43, 1.88 for 1 week, and AOR 1.62, 95% CI 1.39, 1.88 for 1 day) and Z‐drugs (AOR 1.42, 95% CI 1.14, 1.76 for 1 month, AOR 1.37, 95% CI 1.06, 1.75 for 1 week, AOR 1.34, 95% CI 1.03, 1.75 for 1 day), but not antipsychotics. Moreover, significant dose effects of antidepressants (equal to or more than 0.6–1.0 DDD), BZDs (equal to or more than 0.1–0.5 DDD) and Z‐drugs (more than 1 DDD) were observed, respectively, on the risk of experiencing an MVA. Conclusion Taken together, subjects taking antidepressants, BZDs and Z‐drugs, separately, should be particularly cautioned for their increasing risk of MVAs.